FRI0416 Syndecan-1 (CD138), B Lymphocyte Stimulator (BLYS) and their Association with Clinical Variables and Autoantibodies in Systemic Lupus Erythematosus. (9th June 2015) - Fajardo-Robledo, N.S.; Diaz-Rizo, V.; Perez-Guerrero, E.E.; Bonilla-Lara, D.; Saldaña-Anguiano, J.M.; Munoz-Valle, J.F.; Huerta, M.; Trujillo, X.; Gonzalez-Lopez, L.; Gamez-Nava, J.I.
Abstract : Background: Syndecan-1 (CD138) a member of the integral membrane heparin sulfate proteoglycan family expressed by plasma cells, that has a relevant role on modulating leukocyte recruitment, matrix remodeling, maintaining vascular homeostasis and participating in the adequate functioning of glomerular filtration barrier. Recently, a possible association between CD138 levels and renal involvement in systemic lupus erythematosus (SLE) has been reported (1). On the other hand, B lymphocyte stimulator (BLyS) levels have been correlated with disease activity. To date, there is a lack of studies evaluating the relationship between CD138 levels with other pro-inflammatory molecules and autoantibodies implied in the involvement to organs in SLE. Objectives: To evaluate the association between serum levels of CD138, BLyS, anti-DNA and anti-nucleosome antibodies and clinical characteristics of organ involvement in SLE. Methods: We included 85 patients with SLE and 55 healthy controls. We assessed disease characteristics, disease activity score (m-SLEDAI), and clinical and laboratory variables related with organ involvement. Serum levels of CD138, BLyS, anti-DNA and anti-nucleosomes antibodies were quantified by ELISA. In the statistical analysis we evaluated the correlation between CD138 levels and BLyS with clinical and serological variables in SLE. Results: Higher levels of CD138 were observed in SLE compared with controls (104.1±71.2 vs. 83.9±50.4 respectively, p=0.040). Fifty-three (57%) patients with SLE had an active disease according to m-SLEDAI, and 29 (35%) had renal involvement. CD138 correlated positively with proteinuria (r=0.40, p<0.001), anti-DNA titers (r=0.42, p=0.001) and titers of anti-nucleosome antibodies (r=0.30, p=0.014), but did not correlate with serum creatinine (r=0.18, p=0.11). Instead, BLyS levels correlated significantly with higher creatinine serum levels (r=0.34, p=0.001), without a correlation with proteinuria (r=0.06, p=0.6). We did not observe a correlation between CD138 levels and BLyS (r=0.87, p=0.365) reflecting an independence between both biomarkers. Conclusions: These results suggest that CD-138 levels can be an independent biomarker from lupus nephropathy, correlating with proteinuria, anti-DNA and anti-nucleosome antibodies. A potential role of the changes of CD-138 levels as predictive factors for the development of relapses requires be evaluated in future longitudinal studies. This project was financed by a grant of the Fondo de Investigacion en Salud del Instituto Mexicano del Seguro Social: (grant FIS/PROT/G13/1202). References: Ki-Jo Kim, et al, Elevated Serum Levels of Syndecan-1 Are Associated with Renal Involvement in Patients with Systemic Lupus Erythematosus. J Rheumatol. 2014 Dec 15. pii: jrheum.140568. Disclosure of Interest: None declared